2010
DOI: 10.1089/ten.teb.2009.0658
|View full text |Cite
|
Sign up to set email alerts
|

The Design and Use of Animal Models for Translational Research in Bone Tissue Engineering and Regenerative Medicine

Abstract: This review provides an overview of animal models for the evaluation, comparison, and systematic optimization of tissue engineering and regenerative medicine strategies related to bone tissue. This review includes an overview of major factors that influence the rational design and selection of an animal model. A comparison is provided of the 10 mammalian species that are most commonly used in bone research, and existing guidelines and standards are discussed. This review also identifies gaps in the availabilit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
256
0
5

Year Published

2013
2013
2020
2020

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 268 publications
(269 citation statements)
references
References 223 publications
(179 reference statements)
1
256
0
5
Order By: Relevance
“…In targeting the translation of a (bone) tissue engineering approach from bench to bedside, there is a distinct hierarchy and sequence of the type of studies that need to be undertaken to promote the translation process (192): Having identified clinical needs and based on fun- damental discoveries regarding biological mechanisms, a novel tissue engineering approach is designed and first studies are undertaken to characterise mechanical and chemical properties of the TEC to be used. The next step involves feasibility and bioactivity testing and should be carried out in vitro and in vivo.…”
Section: Rationale For Translating Bone Tissue Engineering Strategiesmentioning
confidence: 99%
“…In targeting the translation of a (bone) tissue engineering approach from bench to bedside, there is a distinct hierarchy and sequence of the type of studies that need to be undertaken to promote the translation process (192): Having identified clinical needs and based on fun- damental discoveries regarding biological mechanisms, a novel tissue engineering approach is designed and first studies are undertaken to characterise mechanical and chemical properties of the TEC to be used. The next step involves feasibility and bioactivity testing and should be carried out in vitro and in vivo.…”
Section: Rationale For Translating Bone Tissue Engineering Strategiesmentioning
confidence: 99%
“…For these reasons the sheep is increasingly becoming the animal model of choice for bone tissue engineering research (reviewed in detail by Refs. [1][2][3][4] ). The first sheep genome draft was released in 2009, 5 however, there are still gaps in the annotated sequence information available in the sheep transcriptome, particularly when compared to other species, such as the cow, mouse, rat, or humans.…”
Section: Introductionmentioning
confidence: 99%
“…The two most commonly considered applications for Mg medical devices are in orthopaedics and cardiovascular surgery [1,16,17]. The selection of appropriate animal models which reflect or match the part of the targeted part of the human system most effectively is a topic which gathers much discussion and research in biomedical materials [118,119]. For orthopaedic applications small animal studies are generally conducted in rodents such as rats or rabbits [18,27,120,121].…”
Section: Consideration For Selecting An Appropriate In Vivo Modelmentioning
confidence: 99%